(untitled) (Journal of Economic Research & Business Administration, 2015)
The credit market allows to carry out accumulation, movement, distribution and redistribution of the loan capital between economy spheres. Today the credit market of the Republic of Kazakhstan is the largest element of the financial market of the country. If five years ago the three of banks of the second level was the center of a banking system, today to the forefront there are average banks with the target audience. The RK credit market tends high-quality development. Banks have impact on substantial increase of the competition in the banking sector with the foreign participation which competitive advantage is transfer of innovative technologies from parent banks in the field of automation and reengineering of business processes. Against further strengthening of the competition banks will continue work on increase of efficiency of the current activity, much attention will be paid to quality and service speed, development of remote channels of service for clients. The special attention was paid to development in banks of the centers of postcredit service and their automation that allowed to strengthen control of quality of a credit portfolio, since first day of delay of payments on the credit